GPR65 protects adipose-derived stem cell therapy against acidosis in hindlimb ischemia - Wenhao Niu; Shilei Wan; Wenyue Cao; Huilong Qu; Huihui Yuan; Kun Huang; Jianxiang Wu; Jan Nilsson; Ru Ding; Chun Liang; Yihong Chen (Molecular Medicine, 2026)
Abstract Background Critical limb ischemia is the end stage of lower extremity peripheral artery disease (PAD) with few available pharmacological and endovascular approaches. Stem cell-based therapy represents a promising therapeutic strategy for angiogenesis; however, its clinical benefits have not yet met expectations. Tissue acidosis is a central challenge in stem cell transplantation, and poor cell survival and function of the transplanted cells caused by acidosis-mediated injury limit the therapeutic potential. This study aimed to determine whether GPR65, a proton-sensitive G protein-coupled receptor, improves adipose-derived stem cells (ADSCs) survival in acidic environments and to elucidate the underlying mechanisms. Methods GPR65 expression in ADSCs exposed to acidic conditions and in ischemic muscles were analysed. Subsequently, lentivirus-induced GPR65-overexpressing ADSCs were constructed and subjected to functional and angiogenic assays under low pH conditions. The function of these cells was explored using a mouse hindlimb ischemia model with transplantation of the cells or control medium into the ischemic muscles. Metabolic alterations, blood perfusion recovery, vascular regeneration and transplanted cell survival in the ischemic area were measured during a 14-day follow-up period. Additionally, we investigated the pathways induced by GPR65 using transcriptomic sequencing, proteomic analyses, western blot, and quantitative reverse transcription polymerase chain reaction. Finally, western blot analyses were carried out to determine the role of endogenous GPR65 for adaptation to acidic stress in GPR65 knock-down ADSCs by shRNA. Results We observed significant changes in GPR65 expression in response to acidic and ischemic conditions, both in vitro and in vivo. Genetic overexpression of GPR65 in ADSCs induced protective effects on cell survival, cell proliferation, and dysregulation of mitochondrial dynamics in response to acidosis. Importantly, GPR65 overexpression promoted the angiogenic potential, VEGF-A and HGF secretion. Remarkedly these effects resulted in the improved limb salvage, blood reperfusion, vascular regeneration and retained ADCS in ischemic tissues via the accelerated phosphorylation of the Akt and ERK1/2 pathways. In contrast, GPR65 knock-down impaired VEGF-A expression, Akt and ERK1/2 activation in cultured ADSCs under low pH condition. Conclusion Our study identified GPR65 as a therapeutic target for protection of transplanted stem cells against acidosis-mediated injury. These results suggest that genetically engineered ADSCs expressing GPR65 may be an innovative strategy for the treatment of ischemic vascular diseases.